Review and pictorial essay on complications of bariatric surgery - Raspante,Laio Bastos de Paiva (2020)
SUMMARY Obesity is a chronic disease characterized by excess fat in the body and a real public health problem. Bariatric surgery, in recent decades, has gained space in its treatment due to the efficiency obtained in weight loss and significant reduction of the related comorbidities. The most commonly performed bariatric procedures include Roux-en-Y gastric bypass, adjustable gastric band, and laparoscopic sleeve gastrectomy. Possible complications described include fistulas, dehiscence, marginal ulcers, intestinal obstruction, internal hernias, and anastomotic stenosis. These complications may have unfavorable clinical outcomes since symptoms are often nonspecific. Abdominal computed tomography (CT) is an important tool in the evaluation of postoperative complications, both in the immediate and late postoperative status of patients undergoing such a procedure. We analyzed the most illustrative tomographic findings of the different complications after reducing gastroplasty in 203 patients without distinction of age or gender. Correct interpretation requires radiologists to understand the surgical technique since postoperative anatomy and surgery-specific complications may be obstacles to proper interpretation.